PERAN KEPALA KELUARGA DALAM PENANAMAN NILAI-NILAI AKHLAK - Bahyati; Barja; Ade Imun Romadon; Bidayatul Inayah; Ahmad Munji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of the head of the family in instilling moral values in children aged 6–12 years using the Systematic Literature Review (SLR) method. Scientific articles from Google Scholar, Scopus, and SINTA (2020–2025) were examined through seven stages: identification, selection, quality assessment, data extraction, thematic analysis, synthesis, and conclusion. The selection process applied inclusion criteria (relevant articles, based on scientific research, published between 2020–2025) and exclusion criteria (irrelevant, unavailable in full text, or non-accredited). Core data such as objectives, methods, results, and findings were analyzed thematically across three aspects: role modeling (uswah ḥasanah), educational communication, and religious parenting. The findings indicate that the head of the family plays a central role in shaping children’s moral character. Role modeling emerges as the dominant factor, as elementary school children tend to imitate parental behavior in daily life. Effective and dialogical communication strengthens the internalization of moral values, while religious parenting through worship habituation and spiritual value cultivation contributes to character development. Key challenges include limited parental time and the influence of digital technology, which may alter family interaction patterns. From the perspective of Islamic Religious Education, the role of the head of the family has strong normative foundations in the Qur’an and Hadith, underscoring parental responsibility in nurturing children’s morals. Therefore, integrative, consistent, and adaptive approaches are required to ensure optimal moral education that remains relevant to contemporary dynamics.